Implementation of the International Classification of Functioning, Disability and Health (ICF) in Portuguese Special Education Policy and Practice - Sanches-Ferreira, Manuela (2013)
In January 2008 with the introduction of the Decree-L aw n.º3/2008, Portugal became the first country implementing the International Classification of Functioning, Disability and Health, ICF (WHO, 2001) as a framework to be obligatorily used in special education system. This policy was responsible for the introduction of substantial changes among which the ICF implementation to support the assessment and eligibility processes represented the major challenge for educational professionals.